Remote sensing of chemical agents within nuclear facilities using Raman spectroscopy. (20th November 2020) - Foster, Michael; Wharton, Michael; Brooks, William; Goundry, Matthew; Warren, Charles; Storey, Jonathan
Abstract: The identification and characterisation of radioactive material and other hazardous substances are essential requirements for the nuclear industry. Raman spectroscopy can be used to identify substances; however, given the challenging nature of the environment, instruments typically cannot be located within 1 m of the target substance. A new stand‐off Raman instrument using a spatial heterodyne spectrometer mounted on a remotely operated vehicle (ROV) is presented, and its ability to identify a range of chemicals of interest to the industry is demonstrated within a representative environment. The instrument demonstrated an ability to routinely make Raman observations at 1 m from the target with all sensitive electronic elements situated remotely outside the target environment. Abstract : Raman spectra have been acquired of a uranyl nitrate, tri‐butyl phosphate and kerosene, from within a representative nuclear facility. Demonstrating for the first time the ability to characterize chemical agents within this challenging environment in a same manner using Raman spectroscopy.